Surgical Management of Tempromandibular Joint Ankylosis: An analysis of 20 cases - Shweta Bhatnagar; Anuradha Navneetham (International Journal of Medical Research and Review, 2014)
Introduction: Ankylosis is a Greek term meaning “stiff joint”. The fusion of the articular surfaces of head of condyle with the glenoid fossa leads to TMJ ankylosis. The subarticular layer is composed of a rich vascular network that penetrates the cortical layer. Haemarthrosis of this highly osteogenic layer due to trauma commonly leads to the organization of fibroosseous mass and bony ankylosis can ensue.Method: This clinical study included 22 patients from 2008-2013. Out of these 20 patients underwent surgery. There were 17 patients below 14 years of age and five patients above 14 years. Etiopathogenesis was traumatic in 19 cases, septic in 2 cases and autoimmune in one case.Result: The patients were followed up for one to six years. All patients under treatment showed a distinctive improvement both in articular functionality and symptoms. In two patients recurrence was noticed and they were taken for secondary surgery. The functional results of using temporalis fascia as an interpositional material were satisfactory.Discussion: We conclude that early postoperative physiotherapy and strict follow-up play an important role in preventing postoperative adhesions.